The role of Fanconi anaemia factors in the response to transcription-replication conflict - Langton, J (2018)
Replication and transcription both require large, multi-protein complexes that bind and translocate DNA to facilitate genome duplication and gene expression. This shared requirement inevitably leads to conflict because, despite numerous cellular adaptations, these molecular machines will utilize the same areas of the DNA template during S-phase. This conflict results in transcription being a source of replication stress and ultimately genomic instability. How these conflicts are managed and resolved is poorly understood - the current study attempts to investigate the role of the Fanconi anaemia (FA) pathway in resolving replication stress caused by conflict with transcription. The FA pathway is associated with the repair of interstrand cross-links (ICLs) produced by exogenous agents, but it is not clear if these types of lesions are produced endogenously or represent the only substrate of the FA pathway. Loss of the FA pathway leads to an increased level of transcription associated DNA:RNA hybrids (R-loops) and associated replication defects and damage. The current study demonstrates that these structures are relevant to the pathology of FA, as they accumulate in cells derived from FA patients and in murine haematopoietic stem cells (HSCs). This strongly suggests the FA pathway has a specific role in dealing with cell stress arising from transcription and R-loops. In line with this notion, this study demonstrates that depletion of the transcription-coupled repair factor CSB leads to increased transcription-replication conflicts that requires the action of FA factors. In the absence of FA proteins, the loss of CSB leads to replication fork stalling, mitotic catastrophe and reduced proliferation. Overall, this data supports the growing evidence that the FA pathway is required to respond to conflicts between replication and transcription, as well as transcription-associated R-loops. My data suggests that replication fork collisions with transcription complexes and/or R-loops represents a major substrate of the FA pathway and suggests transcription-replication conflict could contribute to the attrition of HSCs in FA patients.